The Importance of Dictation Activity in Language Teaching - djoubar, abdelhafid; oukali, nadjah (El Omda in Linguistics and Discourse Analysis, 2022)
Dictation is a branch of the Arabic language and a means of communication through which the pupil or individual expresses their ideas. Teaching it enables the learner to understand and acquire a specific writing skill, thereby developing the ability to spell words correctly. We can also infer that dictation has significant psychological importance, as it helps the learner who can write accurately to develop an independent personality and communicate easily with the teacher. In contrast, a weak learner or one unable to write properly may experience psychological distress, as they are unable to convey their ideas or express their understanding to the teacher. The problem addressed in this study revolves around the following questions: – What are the main instructional situations that the teacher addresses through dictation activities? – Is there a relationship between dictation and the overall level of learners and teachers? – What strategies do teachers use when implementing dictation with learners? These are the questions that this research seeks to answer.